ANALYZING THE VOCABULARY CONTAINED IN ENGLISH TEXTBOOKS FOR FIRST GRADE OF SENIOR HIGH SCHOOL - Silvania Sefaca Sipahutar; Raees Narhan; Ratna Paramita; Erikson Saragih (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to analyze the vocabulary contained in the English textbook for the first grade of senior high school. This study focused on the vocabulary presented in the English TextBook for First Grade High School. This research was conducted to solve the issues of the importance of vocabulary as a part of learning content. Based on Tomlinson’s theory, appropriate vocabularies for learning content include textbook. The design of this research was a descriptive qualitative analysis with the book as the main source for gathering the data. The book consisted of fifteen chapters, and each chapter provided vocabulary content. The information on this exploration was the material of English textbook. The result of this research revealed that the English textbook fulfilled 15 measures or 93,7% corresponding with the Tomlinson's theory. In this way, the English textbook was suitable to be used for the students.